The effects of green tea derived catechins upon adipocyte metabolism - Mehra, Anisha (2010)
Tea, from the plant Camellia Sinensis, is after water, the most consumed drink in the world. Green tea, produced by steaming freshly harvested leaves to prevent fermentation, is high in polyphenols known as catechins or flavanols. The major flavanols found in green tea include (-) epigallocatechin-3-gallate (EGCG) and (-) epicatechin. Literature reports suggest that green tea flavanols have the potential to exert anti-obesity effects by modulating weight gain and other factors such as lipogenesis, β-oxidation and adipokine release. Key features of obesity and associated insulin resistance are adipokine dysregulation, decreased sensitivity of adipocytes to insulin and subsequently, changes in glucose uptake by cells.